PROFIL LITERASI LINGKUNGAN PESERTA DIDIK SMAN 3 ADIWIYATA DAN SMAN 16 NON ADIWIYATA DI RUMBAI - Ermina Sari; Raudhah Awal; Martalasari Martalasari; Dwi Andani Pandia (Bio-Lectura : Jurnal Pendidikan Biologi, 2023)
This study aims to study the environmental literacy profile of students at SMAN 3 as Adiwiyata schools and SMAN 16 as Non Adiwiyata schools in Rumbai. The subjects of this study were divided into two groups, the first being class X of SMAN 3 Pekanbaru who received the Adiwiyata predicate. The population of students at this adiwiyata schools was 360 students with a sample of 20 students. The second research subject was SMAN 16 Pekanbaru, class X who had never received the adiwiyata predicate at all. The population of students in this non adiwiyata schools totalled 144 students with a sample of 20 students. This study uses a descriptive method with a survey design. The sampling technique used was cluster random sampling. This study used a questionnaire instrument to measure environmental literacy on the aspects of attitudes and behavior. Based on the results of data analysis, the average score of attitude on caring for the environment was 3,92 in Adiwiyata schools and 3,79 in non-Adiwiyata schools, while the average score for aspects of behaviour on environmental care in Adiwiyata schools was 4,28 and in non-Adiwiyata schools was 4,24. This means that it can be concluded that the environmental literacy profile on the aspects of attitudes and behavior of the adiwiyata schools was higher than the non-Adiwiyata school.